Proteomic profile of extracellular vesicles in maternal plasma of women with fetal death. (31st December 2023) - Gallo, Dahiana M.; Fitzgerald, Wendy; Romero, Roberto; Gomez-Lopez, Nardhy; Gudicha, Dereje W.; Than, Nándor Gábor; Bosco, Mariachiara; Chaiworapongsa, Tinnakorn; Jung, Eunjung; Meyyazhagan, Arun; Suksai, Manaphat; Gotsch, Francesca; et al.
Abstract: Objectives: Fetal death is a complication of pregnancy caused by multiple etiologies rather than being the end-result of a single disease process. Many soluble analytes in the maternal circulation, such as hormones and cytokines, have been implicated in its pathophysiology. However, changes in the protein content of extracellular vesicles (EVs), which could provide additional insight into the disease pathways of this obstetrical syndrome, have not been examined. This study aimed to characterize the proteomic profile of EVs in the plasma of pregnant women who experienced fetal death and to evaluate whether such a profile reflected the pathophysiological mechanisms of this obstetrical complication. Moreover, the proteomic results were compared to and integrated with those obtained from the soluble fraction of maternal plasma. Methods: This retrospective case-control study included 47 women who experienced fetal death and 94 matched, healthy, pregnant controls. Proteomic analysis of 82 proteins in the EVs and the soluble fractions of maternal plasma samples was conducted by using a bead-based, multiplexed immunoassay platform. Quantile regression analysis and random forest models were implemented to assess differences in the concentration of proteins in the EV and soluble fractions and to evaluate their combined discriminatory power between clinical groups. Hierarchical cluster analysis was applied to identify subgroups of fetal death cases with similar proteomic profiles. A p -value of <.05 was used to infer significance, unless multiple testing was involved, with the false discovery rate controlled at the 10% level ( q < 0.1). All statistical analyses were performed by using the R statistical language and environment-and specialized packages. Results: Nineteen proteins (placental growth factor, macrophage migration inhibitory factor, endoglin, regulated upon activation normal T cell expressed and presumably secreted (RANTES), interleukin (IL)-6, macrophage inflammatory protein 1-alpha, urokinase plasminogen activator surface receptor, tissue factor pathway inhibitor, IL-8, E-Selectin, vascular endothelial growth factor receptor 2, pentraxin 3, IL-16, galectin-1, monocyte chemotactic protein 1, disintegrin and metalloproteinase domain-containing protein 12, insulin-like growth factor-binding protein 1, matrix metalloproteinase-1(MMP1), and CD163) were found to have different plasma concentrations (of an EV or a soluble fraction) in women with fetal death compared to controls. There was a similar pattern of change for the dysregulated proteins in the EV and soluble fractions and a positive correlation between the log2 -fold changes of proteins significant in either the EV or the soluble fraction ( ρ = 0.89, p < .001). The combination of EV and soluble fraction proteins resulted in a good discriminatory model (area under the ROC curve, 82%; sensitivity, 57.5% at a 10% false-positive rate). Unsupervised clustering based on the proteins differentially expressed in either the EV or the soluble fraction of patients with fetal death relative to controls revealed three major clusters of patients. Conclusion: Pregnant women with fetal death have different concentrations of 19 proteins in the EV and soluble fractions compared to controls, and the direction of changes in concentration was similar between fractions. The combination of EV and soluble protein concentrations revealed three different clusters of fetal death cases with distinct clinical and placental histopathological characteristics.